FAMILY CONNECTEDNESS AND RISKY SEXUAL BEHAVIOR AMONG ADOLESCENTS WHOSE PARENTS WORK AS MIGRANT WORKERS IN LEMBATA DISTRICT - Rangga, Ina Johoria; Panis, Marleny P.; Takalapeta, Theodora (Journal of Health and Behavioral Science, 2024)
Risky sexual behavior is human behavior driven by sexual desire that can lead to extramarital pregnancy, abortion, sexually transmitted diseases and HIV/AIDS. Adolescents can communicate their reproductive needs with their families, because the role of the family is very important in adolescent puberty. The purpose of the study was to analyze the relationship between family connectedness and risky sexual behavior in adolescents whose parents work as migrant workers. Sampling using quota sampling technique, with 50 respondents. The type of research used is quantitative correlation. Data collection was done using a questionnaire. The results showed that the significance value was 0.128 (p>0.05) and the correlation coefficient was -0.218 which means that there is no relationship between family connectedness and risky sexual behavior in adolescents whose parents work as migrant workers in Lembata district.